2017
DOI: 10.1007/s00122-017-2955-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping and genomics of soybean seed protein: a review and perspective for the future

Abstract: Key message Genetic improvement of soybean protein meal is a complex process because of negative correlation with oil, yield, and temperature. This review describes the progress in mapping and genomics, identifies knowledge gaps, and highlights the need of integrated approaches. AbstractMeal protein derived from soybean [Glycine max (L) Merr.] seed is the primary source of protein in poultry and livestock feed. Protein is a key factor that determines the nutritional and economical value of soybean. Genetic imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
185
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 173 publications
(191 citation statements)
references
References 119 publications
4
185
0
2
Order By: Relevance
“…When the elite genotypes from South Korea (44.06 ± 1.8%) compared with the USA (41.12 ± 1.3%) and China (42.10 ± 1.4%), Korean elite lines showed a significantly higher protein. It has been reported that geographical origin and maturity groups are the principal determinants of population structure and phenotypic variation and accessions from Korea form a unique population structure compared with Chinese and US accessions (Patil et al ., ). Furthermore, GWAS for protein content based on geographical origin identified the strongest association on Chr.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…When the elite genotypes from South Korea (44.06 ± 1.8%) compared with the USA (41.12 ± 1.3%) and China (42.10 ± 1.4%), Korean elite lines showed a significantly higher protein. It has been reported that geographical origin and maturity groups are the principal determinants of population structure and phenotypic variation and accessions from Korea form a unique population structure compared with Chinese and US accessions (Patil et al ., ). Furthermore, GWAS for protein content based on geographical origin identified the strongest association on Chr.…”
Section: Resultsmentioning
confidence: 97%
“…The heritability of measured traits was calculated based on the analysis of variance of family means (Table S1). It is well studied that seed protein content is negatively correlated to seed oil and sucrose content in soybean (Nichols et al ., ; Patil et al ., ; Sonah et al ., ) Based on the phenotypic correlation among traits estimated for protein, oil, and sucrose across four environments, a similar trend was observed in this population (Figure ). Moreover, the phenotypic data presented in this study supported the fact that soybean seed composition is significantly affected by environmental conditions (Bandillo et al ., ; Chaudhary et al ., ; Thomas et al ., ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…is an important legume crop in the world, domesticated mainly for its high oil and protein contents (Patil et al 2017). Major constituents of soybean seeds are protein (∼40%), carbohydrate (∼34%), oil (∼21%), and ash (∼5%) (Burton 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to specialty cultivars with trait‐specific breeding objectives, such as high protein, rather than solely yield improvement. As the genetic basis of the oil and protein relationship is complex and still poorly understood, a number of questions remain to be addressed (Patil et al, 2017).…”
Section: Discussionmentioning
confidence: 99%